2020
DOI: 10.1371/journal.pone.0229130
|View full text |Cite
|
Sign up to set email alerts
|

Automaticity in processing spatial-numerical associations: Evidence from a perceptual orientation judgment task of Arabic digits in frames

Abstract: Human adults are faster to respond to small/large numerals with their left/right hand when they judge the parity of numerals, which is known as the SNARC (spatial-numerical association of response codes) effect. It has been proposed that the size of the SNARC effect depends on response latencies. The current study introduced a perceptual orientation task, where participants were asked to judge the orientation of a digit or a frame surrounding the digit. The present study first confirmed the SNARC effect with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Both channels are simultaneously activated. The numerical‐spatial representation can be completed through a fast unconditional route when the S–R rule is congruent (i.e., left‐hand response to small numbers and right‐hand response to large numbers); however, it needs to pass through the slow conditional route when the S–R rule is incongruent, which was solved in the response selection stage (Didino et al, 2019; Gevers et al, 2010; Gevers, Ratinckx, et al, 2006; Herrera et al, 2008; Wu et al, 2020; Yu et al, 2020).…”
Section: Previous Theoretical Accounts Of the Snarc Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Both channels are simultaneously activated. The numerical‐spatial representation can be completed through a fast unconditional route when the S–R rule is congruent (i.e., left‐hand response to small numbers and right‐hand response to large numbers); however, it needs to pass through the slow conditional route when the S–R rule is incongruent, which was solved in the response selection stage (Didino et al, 2019; Gevers et al, 2010; Gevers, Ratinckx, et al, 2006; Herrera et al, 2008; Wu et al, 2020; Yu et al, 2020).…”
Section: Previous Theoretical Accounts Of the Snarc Effectmentioning
confidence: 99%
“…Participants are assumed to be required to judge the parity of numbers and use the “left‐odd and right‐even” rule to make a response. When a small number (e.g., 2) is presented, it automatically activates the magnitude representation of this digit (Aleotti et al, 2020; Cooney et al, 2021; Didino et al, 2019; Gevers et al, 2010; Gevers, Lammertyn, et al, 2006; Gevers, Ratinckx, et al, 2006; Hartmann et al, 2019; Herrera et al, 2008; Sixtus et al, 2019; Vicovaro & Dalmaso, 2020; Weis et al, 2018; Wu et al, 2020; Yu et al, 2020) and spatial attention (Nikolaev et al, 2020; Rasoulzadeh et al, 2021; Sahan et al, 2022; Van Dijck et al, 2014). The numerical magnitude representation quickly activates the verbal concept of “small number” and the linked “left” concept (Gevers et al, 2010).…”
Section: Cognitive Control In Two Stages Of the Snarc Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the aforementioned concerns, researchers have developed other tasks to more thoroughly assess whether explicit magnitude processing is necessary for the construction of d-SNAs. For example, instead of magnitude comparison, or parity, judgements, participants might complete a judgement of the perceptual, non-numerical feature of the stimulus display, such as the font colour or stimulus orientation (Fias et al, 2001;Mitchell et al, 2012;Yu et al, 2020). Such work has found that judgements of orientation (Mitchell et al, 2012;Yu et al, 2020), but not colour (Fias et al, 2001;Mitchell et al, 2012), induced d-SNAs, suggesting that in some cases, d-SNAs may occur in the absence of any explicit numerical processing.…”
Section: Introductionmentioning
confidence: 99%
“…Relative numerousness judgment is the simplest form of numerical competence, represented by discrimination between two quantities [3]. Subtilizing was elaborated and defined as the "immediate, correct assignation of number words to small collections of perceptual items", emphasizing that it is basically a perceptual process, rather than a cognitive one [4].…”
Section: Introductionmentioning
confidence: 99%